KEBERSIHAN GIGI DAN MULUT PADA ANAK TUNARUNGU DI SLB KABUPATEN BANDUNG, MANADO, MAGELANG (STUDI LITERATUR) (Politeknik Kesehatan Kemenkes Bandung, 2021)
According to the Indonesian Ministry of Health in 2010, the number of deaf children in special schools throughout Indonesia was 5,610 people. This study aims to analyze differences in the results of dental and oral hygiene in deaf children in special schools in Bandung, Manado, and Magelang districts. The research method used is descriptive research with literature study, namely the collection of data collected, selected, searched, presented, and analyzed. The results of the literature review according to research’s in Bandung District stated that the OHI-S criteria for deaf children contained moderate and poor OHI-S criteria. The results of the research in Manado stated that the OHI-S of deaf children had good and moderate criteria. Meanwhile, the results of research conducted in Magelang City stated that the OHI-S of deaf children had good and moderate criteria. Thus, it can be concluded that the diversity of OHI-S in deaf children in special schools cannot be separated from various factors that influence it, such as the condition of their disability, as well as the role of caregiver/helper/parents.